Isolating and characterizing antimicrobial peptides derived from larvae of the blowfly Sarconesiopsis magellanica (diptera: Calliphoridae) (2019)
Larval therapy (LT) is an alternative treatment which uses fly larvae to heal chronic wounds; its action is based on debridement, bacterial removal and stimulating granulation tissue. The most important mechanism for fighting infection with LT depends on larval excretions and secretions (ES). The larvae are protected by an antimicrobial peptide (1) spectrum. Sarconesiopsis magellanica is a promising necrophagous fly for use in medicine. This study was thus aimed at identifying and characterizing S. magellanica AMPs contained in ES, for the first time. ES were fractionated by RP-HPLC using C18 columns. The products were lyophilized, and their antimicrobial activity characterized. The sequences were determined by mass spectrometry. The mechanism of action was evaluated by fluorescence and electronic microscopy. Toxicity was tested on HeLA cells and human erythrocytes; the physicochemical properties of the identified peptides were evaluated. Two molecules in the ES were characterized: sarconesin (a new peptide having antibacterial activity against Gram-negative (Escherichia coli D31, Pseudomonas aeruginosa 27853) and Gram-positive (Staphylococcus aureus ATCC 29213, Micrococcus luteus A270) bacteria and sarconsesin II, having activity against Gram-negative (E. coli MG1655, P. aeruginosa ATCC 27853) and Gram-positive (S. aureus ATCC 29213, M. luteus A270) bacteria. The minimum inhibitory concentrations ranged from 1.2 μM upwards; the AMPs did not have toxicity in any tested cells and their action on bacterial membrane and DNA was confirmed. Sarconesin had similarity with the CDC42 protein belonging to the Rho-family of GTPases which are important in organelle development and wound repair. Sarconesin II was seen to be a conserved domain of the ATP synthase protein belonging to the FliI superfamily. The data reported here indicates that the peptides could be alternative therapeutic candidates for use in infections against Gram-negative and Gram-positive microorganisms and as new resources to combat resistance against antimicrobial agents.